2008
DOI: 10.1007/s00520-007-0373-1
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in cancer patients on morphine

Abstract: Constipation affects a large proportion of cancer patients taking oral morphine. Constipation in these patients is generally inadequately treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 28 publications
6
51
2
2
Order By: Relevance
“…Neuropathic action of narcotics in the ENS is expressed as constipation at the whole animal level of organization [20,21]. Opiates and opioids induce non-propulsive intestinal motility and suppress mucosal secretion of H 2 O and electrolytes, each of which reflects suppression of excitability in ENS motor neurons [22][23][24].…”
Section: Enteric Neuropathy Drug-induced Neuropathymentioning
confidence: 99%
“…Neuropathic action of narcotics in the ENS is expressed as constipation at the whole animal level of organization [20,21]. Opiates and opioids induce non-propulsive intestinal motility and suppress mucosal secretion of H 2 O and electrolytes, each of which reflects suppression of excitability in ENS motor neurons [22][23][24].…”
Section: Enteric Neuropathy Drug-induced Neuropathymentioning
confidence: 99%
“…In spite of the small number of patients, these results may be considered similar to the international literature 17,18 and are attributed, in addition to the drugs, to the fact that the study was prospective and that specific attention was given to constipation. It is worth reminding that, according to the literature, constipation secondary to morphine affects 70% to 80% of terminal patients and is difficult to contro l7, 13,14,19 . Our study has shown that it was possible to control constipation for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Constipation in most patients is generally inadequately treated. Although a survey in the UK showed that, for 75% of patients, no change in the perception of constipation was observed and severity of constipation was overestimated by nurses, 4 in an analysis of randomized comparative trials, all the laxatives demonstrated a limited level of efficacy and a significant number of patients required rescue treatments. 5 The literature about the use of laxatives by palliative care units shows that appropriate doses of laxatives are not commonly administered.…”
Section: Introductionmentioning
confidence: 97%
“…5 The literature about the use of laxatives by palliative care units shows that appropriate doses of laxatives are not commonly administered. 4 Moreover, a combination of drugs acting with different mechanisms is only minimally reported. 3 This topic remains controversial because there is no scientific evidence on the treatment of constipation.…”
Section: Introductionmentioning
confidence: 99%